2008
DOI: 10.1097/fbp.0b013e32831c3b06
|View full text |Cite
|
Sign up to set email alerts
|

Selective dopamine D4 receptor agonist (A-412997) improves cognitive performance and stimulates motor activity without influencing reward-related behaviour in rat

Abstract: Current therapies for attention deficit hyperactivity disorder comprise psychostimulants, which block the dopamine transporter and/or stimulate the release of dopamine, leading to a global elevation in extrasynaptic dopamine. These drugs are, however, associated with a series of unwanted side effects such as insomnia, anorexia, headache, stomach problems and potential drug abuse. Recent evidence suggests that the dopamine D4 receptor may represent a selective dopamine target that could mediate cognitive as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 61 publications
3
45
0
Order By: Relevance
“…Accordingly, it seems reasonable to postulate that DRD4 is a key component in the reinstatement of nicotine-seeking behavior, but its activation alone is insufficient for inducing reinstatement of nicotine-taking behavior. In addition, using the drug-conditioned placepreference paradigm, it was also reported that another selective DRD4 agonist (A-412997) does not produce conditioned place preference, a measure of reward in rats (Woolley et al, 2008), although there no information is available for the effect of DRD4 antagonists on rewardrelated behavior with the place-preference paradigm. Future studies should examine the potential interaction between DRD4 and DRD1-like or other DRD2-like subtypes during reinstatement of nicotine-seeking behavior.…”
Section: Discussionmentioning
confidence: 98%
“…Accordingly, it seems reasonable to postulate that DRD4 is a key component in the reinstatement of nicotine-seeking behavior, but its activation alone is insufficient for inducing reinstatement of nicotine-taking behavior. In addition, using the drug-conditioned placepreference paradigm, it was also reported that another selective DRD4 agonist (A-412997) does not produce conditioned place preference, a measure of reward in rats (Woolley et al, 2008), although there no information is available for the effect of DRD4 antagonists on rewardrelated behavior with the place-preference paradigm. Future studies should examine the potential interaction between DRD4 and DRD1-like or other DRD2-like subtypes during reinstatement of nicotine-seeking behavior.…”
Section: Discussionmentioning
confidence: 98%
“…In vivo administration to monkey for cognitive and memory tests [192]; in vitro autoradiography studies [193,194] NRA 0160 0.5 Tested for antipsychotic activity in animal models [195,196] CI 1030 4.3 Tested for antipsychotic activity in animal models [195,196] A-412997 7.9 D4 receptor agonist; improves cognitive performance and stimulates motor activity in rats [197] ADHD is predominantly a condition of childhood, and is characterized by symptoms such as inattention, hyperactivity and distraction. ADHD is thought to affect up to 6% of children [141], and evidence from family data and twin studies suggests that ADHD is familial and heritable [141][142][143].…”
Section: Dopamine-related Diseasesmentioning
confidence: 99%
“…Nevertheless, it has also been suggested that increased PFC dopamine and/or acetylcholine release may underpin the improvements in SOR induced by the D3 antagonist S33138 (4 h; Millan et al 2008Millan et al , 2010 and the D4 receptor agonist A-412997 (24 h; Woolley et al 2008). Since both of these drugs were given systemically, their effect on SOR may well have been mediated outside the PFC (see Beaulieu and Gainetdinov 2011), although the D4 agonist had no effect on hippocampal noradrenaline or acetylcholine release.…”
Section: Introductionmentioning
confidence: 99%